A Case With In Possible Plexiform Neurofibroma - Demir, Tamer; Akyol, Nuray; Yıldırım, Hanifi; Yıldırım, Süleyman (Fırat University, 2001)
6 years old female patient referred for a mass over the right upper eyelid and ptosis, also revealed co-existing bilateral Lisch nodules and cafe-au-laid spots . MRI graphics revealed plexiform neurofibroma extending from right upper eyelid to cavernous sinus and trigeminal nerve. We concluded that one should make the differential diagnosis especially patients presented, during first decade of life, with mass over the upper eyelid and ptosis

Sağ üst kapakta kitle ve ptozisi olan 6 yaşındaki kız hastada, her iki irisde Lisch nodülleri ve vücudunda cafe-au-lait lekeleri tespit edildi. Yapılan MRI incelemesinde sağ üst göz kapağından orbita içine uzanan, kavernöz sinüs ve trigeminal sinir trasesi boyunca ilerlemiş pleksiform nörofıbroma ile uyumlu görüntü elde edildi. Özellikle ilk dekatta üst göz kapağında kitle ve ptozisi olan olgularda pleksiform nörofibromamn ayırıcı tanıda mutlaka irdelenmesi gerektiği sonucuna varıldı.
MUHTEMEL PLEKSİFORM NÖROFİBROMALI BİR OLGU